2021
DOI: 10.1016/j.pedneo.2020.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Safety of vaginal delivery in women infected with COVID-19

Abstract: Objective There is limited data regarding the safety of vaginal delivery in women infected with COVID-19. Our goal was to assess the safety of vaginal delivery in women infected with COVID-19 and the risk of neonatal infection. Study design This was a single medical center cohort study. Data were collected about the outcome of twenty-one women with laboratory-confirmed COVID-19 infection who delivered between March 23, 2020, and May 8, 2020. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Of 27 studies, six (22%) were from China [6] , [7] , [8] , [9] , [10] , [11] ; five (19%) were from Italy [12] , [13] , [14] , [15] , [16] ; three from Spain [17] , [18] , [19] ; two each from Chile [20] , [21] , Turkey [22] , [23] and the United States of America [24] , [25] ; one each from Brazil [26] , France [27] , India [28] , Israel [29] , Mexico [30] , Panama [31] and Peru [32] . Fifteen were classified as high-income countries [24] , [25] , [27] , [29] , [31] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] and 12 as low and middle-income countries [22] , [23] , [26] , [28] , [30] , [32] , [6] , [7] , [8] , [9] , [10] , [11] . Sixteen studies had a retrospective cohort design [14] , [24] , [28] , [29] , [32] , [6] , [7] , [8] , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 27 studies, six (22%) were from China [6] , [7] , [8] , [9] , [10] , [11] ; five (19%) were from Italy [12] , [13] , [14] , [15] , [16] ; three from Spain [17] , [18] , [19] ; two each from Chile [20] , [21] , Turkey [22] , [23] and the United States of America [24] , [25] ; one each from Brazil [26] , France [27] , India [28] , Israel [29] , Mexico [30] , Panama [31] and Peru [32] . Fifteen were classified as high-income countries [24] , [25] , [27] , [29] , [31] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] and 12 as low and middle-income countries [22] , [23] , [26] , [28] , [30] , [32] , [6] , [7] , [8] , [9] , [10] , [11] . Sixteen studies had a retrospective cohort design [14] , [24] , [28] , [29] , [32] , [6] , [7] , [8] , …”
Section: Resultsmentioning
confidence: 99%
“…Fifteen were classified as high-income countries [24] , [25] , [27] , [29] , [31] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] and 12 as low and middle-income countries [22] , [23] , [26] , [28] , [30] , [32] , [6] , [7] , [8] , [9] , [10] , [11] . Sixteen studies had a retrospective cohort design [14] , [24] , [28] , [29] , [32] , [6] , [7] , [8] , [9] , [10] , [17] , [18] , [19] , [20] , [21] , [22] and 11 a prospective cohort design [15] , [16] , [23] , [30] , [31] , [11] , [12] , [13] , [25] , [26] , [27] . There were no randomised controlled trials.…”
Section: Resultsmentioning
confidence: 99%
“…Emerging reports have reported SARS-CoV-2 being detected in amniotic uid, vaginal uid and the placenta [20,21], highlighting the possibility of infection in utero and during delivery. Systematic review of cases reported in the literature have indicated no substantial evidence for increased transmission risk during vaginal birth [28][29][30][31]. Even so, most of the women in our cohort had expressed uncertainty regarding the optimal mode of delivery in women with COVID-19.…”
Section: Discussionmentioning
confidence: 75%
“…Parturients with COVID-19 were managed in similar fashion to healthy women with the mode of delivery dictated by obstetric indications as shown safe in previous studies [16,17]. This is contrary to many reports during the early phase of the pandemic, mainly from China, that showed an increased rate of cesarean deliveries [18].…”
Section: Discussionmentioning
confidence: 91%